Potential Secondary Metabolites in Guava (Psidium guajava) Assisted by Radar Chart Analysis (RCA) and Area Under Curve (AUC) - Cendekiawan, Khrisna Agung; Kintoko, Kintoko; Yuliani, Sapto; Anggraeni, Linda Suci (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2025)
Background:  Diarrhea is a common health problem worldwide, with causes ranging from microbial infections to gastrointestinal disorders. Conventional diarrhea treatments usually involve synthetic drugs, but medicinal plant-based therapies, such as those containing secondary metabolite compounds in guava leaves, show promising potential. In this systematic review, we aimed to identify potential metabolite compounds.Objective: In this systematic review, we aim to identify potential secondary metabolite compounds in medicinal plants with antidiarrheal effects and explore the biological mechanisms of action involved.Methods: Using a literature review, relevant articles were analyzed from reputable scientific databases.Results: The results of the review indicate that compounds such as flavonoids, polyphenols, tannins, and saponins in guava leaves possess antidiarrheal potential, contributing to the regulation of intestinal motility, inhibition of inflammation, and alteration of the gut microbiota composition.Conclusion: The results of this study indicate that medicinal plants and their secondary metabolites can be a promising alternative for safer and more efficient antidiarrheal therapy.